Physiological, Heamatological, Biochemical and Endocrinological Profiles Changes in Crossbred Cows Affected With Metritis under Tropical Island Ecosystem - Perumal, P.; De, A. K.; Sunder, Jai; Bhattacharya, D. (International Journal of Bio-resource and Stress Management, 2022)
Present study was carried out to assess the haematological, physiological, antioxidant, oxidative stress and endocrinological profiles changes in crossbred cows affected with metritis under the humid tropical island ecosystem of Andaman and Nicobar Islands. The cows affected with clinical metritis as group 2 (n=6) and without metritis as group 1 (n=6) were selected for the present study. These cows were selected in the same locality and similar type of management. Physiological profiles, heamatological profiles, antioxidant and oxidative stress profiles and hormone profiles were estimated. The result revealed that the crossbred cows with metritis were suffered severe anaemia. The metritis affected animals had significantly (p<0.05) low levels of antioxidant profiles and higher malondialdehyde (MDA) levels than the unaffected animal groups. Similarly, endocrinological profiles revealed that the metritis affected animals had significantly (p<0.05) higher levels of cortisol and lower level of estradiol 17β (E2), progesterone (P4), follicle stimulating hormone (FSH), luteinizing hormone (LH) and thyroxine (T4) than the unaffected crossbred cows. These heamatological parameters have shown significant (p<0.05) positive correlation with follicle stimulating hormone, luteinizing hormone, estradiol 17β, progesterone, thyroxine and antioxidant profiles whereas significant (p<0.05) negative correlation was observed with malondialdehyde, cortisol, TWBC and total differential count. It was concluded that the metritis was due to anaemia, lack of antioxidants, over production of free radicals and disturbances of endocrinological profiles in crossbred cows of Andaman and Nicobar Islands. A balanced ration with good quality and quantity of antioxidants, sufficient daily exercise and sufficiently clean drinking water can minimize the metritis percentage in the crossbred cows.